Capsaicin for cardiometabolic syndrome: multitarget mechanisms and therapeutic potential - Lin, Jinyuan; Shen, Honglei; Ou, Huajin; Luo, Huilin; Huang, Dongqin; Ye, Liu (Frontiers in Nutrition, 2026)
Cardiometabolic syndrome (CMS) is a multifactorial disorder characterized by the clustering of central obesity, insulin resistance, atherogenic dyslipidemia, hypertension, and chronic low-grade inflammation, collectively predisposing individuals to type 2 diabetes and increased cardiovascular morbidity and mortality. Capsaicin, the principal bioactive compound derived from chili peppers, has attracted growing interest as a multitarget modulator of the complex pathophysiology underlying CMS. Accumulating evidence indicates that capsaicin confers cardiometabolic protection predominantly through transient receptor potential vanilloid 1 (TRPV1)-mediated signaling, while additional TRPV1-independent mechanisms may also contribute. These actions include enhancement of energy metabolism, improvement of insulin sensitivity, suppression of inflammatory and oxidative pathways, regulation of lipid homeostasis, and preservation of vascular function. Recent studies highlight the importance of a capsaicin–gut microbiota axis, whereby capsaicin reshapes microbial composition, modulates bile acid and short-chain fatty acid signaling, and reinforces intestinal barrier integrity, thereby exerting systemic metabolic and cardiovascular benefits. Despite compelling mechanistic and preclinical evidence, translation to clinical application remains limited by variability in effective dosing, bioavailability, and interindividual differences in gut microbiota composition. This review synthesizes current advances in the molecular and physiological actions of capsaicin and discusses future perspectives for its clinical development as an adjunctive strategy for CMS management.